Maternal mortality in the Callejon de Huaylas (1981-1995) Region Chavin - Mosquera, Vidal (2015)
First descriptive study on the 42 maternal deaths registered during the past ten years (1985-1995) at all five Callejón de Huaylas Hospitals and 16 011 live newborns, representing 262,3 deaths per 100 000 live newborns. Death occurred most frequently between 20 and 40 years old and with parity less than 3. Marital status, education and homework were similar to other investigations. Prenatal control was abscent or sufficient in 78,5%. Direct maternal deaths represented 80,9% and death during the puerperium was 73,5%. Direct causes were mainly puerperal infection, toxemia, abortion and hemorrhage. Indirect causes represented 19% and included anesthesia and one case of bartonellosis. Most patients died before 72 hours of hospital stay. Maternal mortality has decreased form 596,8 (1985) to 392,8 (1994). We consider 40,5% (17 cases) of maternal deaths were avoidable and 25 (59,5%) unavoidable.